Clinical characteristics and short-term outcomes of Japanese encephalitis in pediatric and adult patients: a retrospective study in Northern China - Zhang, Fangyuan; Xu, Guangyin; Zhang, Xiaoyu; Li, Yue; Li, Dong; Wang, Chunjuan; Guo, Shougang (Frontiers in Neurology, 2023)
Objective The study aimed to compare the clinical characteristics and short-term outcomes of pediatric and adult Japanese encephalitis (JE) patients in order to find out the differences. Methods From August 2006 to October 2019, 107 patients (62 pediatric patients and 45 adult patients) with JE were enrolled. Clinical characteristics and short-term outcomes were analyzed. The short-term outcome of each patient was defined as a good outcome or poor outcome according to their Glasgow Coma Scale (GCS) scores (GCS > 8 vs. GCS ≤ 8) at discharge. Results As for acute complications, the incidence of pulmonary infection was higher in 25 adults (25/45, 55.6%) than in 19 children (19/62, 30.6%; P = 0.01). Upper gastrointestinal bleeding was more common in patients with pulmonary infection, with 10 of these patients experiencing the symptom (10/44, 22.7%) compared to only one patient without pulmonary infection (1/63, 1.6%; P = 0.001). The proportion of mechanical ventilation and admission to the intensive care unit (ICU) for supportive care was higher in patients with pulmonary infection than in patients without infection (P < 0.001, P = 0.008, respectively). The GCS scores at discharge in patients with pulmonary infection (7, 4–12.75) were lower than in patients without pulmonary infection (14, 10-14; P < 0.001). Although the GCS scores at the admission of children (9.5, 7–13) were similar to that of adults (7, 6–13), the GCS scores at the discharge of adults (7, 3.5–13) were lower than that of children (13, 10.75–14; P < 0.001). Conclusion The short-term outcome of JE was worse in adults. Pulmonary infection was correlated with a high incidence of upper gastrointestinal bleeding, mechanical ventilation, and ICU hospitalization in JE. Pulmonary infection is a prognostic predictor of short-term outcomes in patients with JE. Vaccination for adults should be initiated.